1986
DOI: 10.1111/j.1467-6486.1986.tb00436.x
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Change: A Psychoanalytic Critique of Argyris and Schon's Contributions to Organization Theory and Intervention

Abstract: The purpose of this essay is to examine psychoanalytically Argyris and Schon's contributions to organization theory and intervention. The author focuses his attention on the problem of individual and organizational resistance to change in the light of Argyris and Schon's cognitive psychological assumptions about learning, reasoning, and effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0
2

Year Published

1994
1994
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 11 publications
1
60
0
2
Order By: Relevance
“…The question is: "How one can use the rich data on resistance to change faculty attitudes?" Several authors propose to "re-think" resistance to change in order to help employees go through the change process in an organization (Diamond, 1986;Piderit, 2000;Oreg, 2006). The factors of resistance vary from one research study to another, as well as the recommendations for improving this situation.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The question is: "How one can use the rich data on resistance to change faculty attitudes?" Several authors propose to "re-think" resistance to change in order to help employees go through the change process in an organization (Diamond, 1986;Piderit, 2000;Oreg, 2006). The factors of resistance vary from one research study to another, as well as the recommendations for improving this situation.…”
Section: Methodsmentioning
confidence: 99%
“…The Change Resistance Theory (Diamond, 1986;Piderit, 2000;Oreg, 2006) has been lately receiving a lot of attention in scholarly literature. Several authors propose to "rethink" resistance to change in order to help employees going through the change process in an organization (Diamond, 1986;Piderit, 2000;Oreg, 2006).…”
Section: The Change Resistance Theory and Control Theory In Relation mentioning
confidence: 99%
See 2 more Smart Citations
“…However, they came to realize that overcoming organizational defensive routines is not as easy as they had at first thought. Diamond (1986) argues that both of these scholars tried to find an answer to these defenses in the cognitive potential of individuals, but that any answer to the psychological/emotional regression needs to be found in a psychodynamics paradigm. Vince (2001Vince ( , 2002, researching in psychodynamics, observed that a relationship of interdependence exists between an organization's management and employees, in a relatedness, which "implies a range of emotional levels of connection across the boundaries of person, role and organization, which emphasize the relational nature of organizing" (Vince 2001(Vince , pp.…”
Section: Olmentioning
confidence: 99%